Problematyka religijno-moralna w prozie wiejskiej XX wieku (W. Astafjew, W. Rasputin, W. Szukszyn) - Popiel-Machnicki, Wawrzyniec (Studia Rossica Posnaniensia, 2011)
Victor Astafiev, Valentin Rasputin and Vasiliy Shukshin are the representatives of a rural Russian prose. They all come from Siberia that has a great impact on their works. They wanted to save the rural spirit, hidden in the endless forests of the taiga, from the destructive influence of the urban culture. The writers wanted the Siberian countryside to help Russian society, which was drawn away from cultural roots, to return again to God.